Social Support, Husnuzan, and Resilience among the Prisoners - Agustin, Lusiana; Nashori, Fuad; Tetteng, Basti; Musa, Muwaga (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Resilience is necessary for the prisoners who are subjected to legal sanctions in accordance with criminal cases committed. Therefore, this study aimed to identify the resilience of the prisoners living in a prison regarding social support and husnuzan. A quantitative correlational method was used to explore the relationship between social support, husnuzan, and resilience. The participants were Muslim male prisoners, aged 18 to 60 years, incarcerated for the first time at Correctional Institution “X” in Yogyakarta. A total of 206 participants were obtained using a purposive sampling method and data were collected through three psychological scales, namely resilience, social support, and husnuzan. The result showed that there was a positive relationship between social support & husnuzan and the resilience of the prisoners. This implies that the prisoners have high resilience when there is a positive thought about the future, as well as receive love and support from family and friends.